SEQUENCE POLYMORPHISM OF MITOCHONDRIAL DNA HYPERVARIABLE REGIONS I AND II IN MALAY POPULATION OF MALAYSIA - Tuladhar, Bhinu Shova; Rashid, Nur Haslindawaty Abd; Panneerchelvam, Sundarajula; Nor, Norazmi Mohd (Scientific World, 2015)
The analysis of the control region of human mitochondrial genome (mtDNA) especially hypervariable regions I (HVI) and II (HVII) segments have been proven to be useful for human identification. For forensic application of mtDNA profiling in Malaysia, a comprehensive database on both HVI and HVII regions are essential. In order to identify polymorphic positions and to determine their frequency in the Malay population, mtDNA HVI and HVII regions of 103 maternally unrelated individuals were amplified ,sequenced and compared with Cambridge reference sequence (CRS). Sequence comparison led to the identification of a total of 446 and 604 location polymorphisms in mtDNA HVI and HVII regions respectively. This polymorphisms defined by 88 haplotypes (81 unique) in the HVI and 78 haplotypes (64 unique) in the HVII regions. In combined HVI and HVII defined 101 haplotypes (99 unique) was defined. In the HVII region All the individuals in HVII showed nucleotide transition event from A G at nucleotide position 073 and 263 and an insertion of cytosine (315.1C) at nucleotide position 315. The genetic diversity and probability of random match in combined HVI and HVII of 103 Malay individuals was found to be 0.9996 and 0.0101 respectively. Scientific World, Vol. 12, No. 12, September 2014, page 24-29